2016
DOI: 10.5551/jat.30452
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and Pharmacodynamics of Lomitapide in Japanese Subjects

Abstract: Aims: Lomitapide is a licensed treatment for patients with homozygous familial hypercholesterolaemia in the USA, the EU, Canada, and Mexico. This study was conducted to compare the pharmacokinetics (PK), pharmacodynamics, safety, and tolerability of lomitapide between Japanese and Caucasian subjects with elevated low-density lipoprotein cholesterol (LDL-C) after single and multiple doses. Methods: In this randomized, double-blind, placebo-controlled study, 36 Japanese and 36 Caucasian subjects with LDL-C level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…The microsomal triglyceride transfer protein inhibitor, lomitapide, is an orally administered agent and the mechanism underlying its LDL-C lowering effect is independent of LDL receptor activation. However, abdominal pain, diarrhea, liver dysfunction and fatty liver have been reported as adverse effects of this drug and although it has been already approved for use in adult patients with HoFH in Japan, it is not approved for childhood HoFH at present 40 , 41 ) .…”
Section: Treatment Of Pediatric Fhmentioning
confidence: 99%
“…The microsomal triglyceride transfer protein inhibitor, lomitapide, is an orally administered agent and the mechanism underlying its LDL-C lowering effect is independent of LDL receptor activation. However, abdominal pain, diarrhea, liver dysfunction and fatty liver have been reported as adverse effects of this drug and although it has been already approved for use in adult patients with HoFH in Japan, it is not approved for childhood HoFH at present 40 , 41 ) .…”
Section: Treatment Of Pediatric Fhmentioning
confidence: 99%
“…17, 22–24) . The results of the current study were also in line with the real-world results reported from a global observational registry prospectively assessing the long-term safety and effectiveness of lomitapide in real-life clinical practice (the LOWER study).…”
Section: Discussionmentioning
confidence: 99%
“…This dose is supported by previously reported pharmacokinetic results in Japanese patients. 24) . MTD was defined as the highest dose during Weeks 0–26 that did not result in unacceptable adverse events (AEs), including elevated liver function tests (LFTs).…”
Section: Methodsmentioning
confidence: 99%